2014
DOI: 10.4028/www.scientific.net/msf.808.51
|View full text |Cite
|
Sign up to set email alerts
|

Machining of WC-Co Composites - A Review

Abstract: This article aims to present a review on the machining of tungsten carbide-cobalt composite material. WC-Co based materials are extensively used where the demand for high performance materials exists because these have the distinguished set of properties such as high hardness, superior wear resistance, high mechanical strength and good dimensional stability. Due to these excellent properties, it serves most applications in the field of tool and die making. Machining of the WC-Co materials is very difficult wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The best way of creating custom surface textures is through laser ablation of WC-Co green compact inserts. Contrarily to sintered WC-Co, this method minimizes the problems of creating spatter, heat-affected zones, and microcracks, with the additional advantages of improving machining efficiency and reducing cost [21,42]. WC-10 wt.% Co green compacts inserts were pressed at Palbit S.A. company.…”
Section: Surface Micro-textures Implementationmentioning
confidence: 99%
“…The best way of creating custom surface textures is through laser ablation of WC-Co green compact inserts. Contrarily to sintered WC-Co, this method minimizes the problems of creating spatter, heat-affected zones, and microcracks, with the additional advantages of improving machining efficiency and reducing cost [21,42]. WC-10 wt.% Co green compacts inserts were pressed at Palbit S.A. company.…”
Section: Surface Micro-textures Implementationmentioning
confidence: 99%
“…In this study, LAJECM machine is used for drilling holes in the WC-Co composite. WC-Co possesses high hardness, superior toughness, high abrasion resistance and good dimensional stability (Kataria and Kumar, 2015b). WC-Co has found a wide range of applications in the industry for the manufacturing of various parts and components (Kataria et al , 2016d).…”
Section: Experimental Planning and Optimizationmentioning
confidence: 99%
“…Based on the literature review on the machining of WC-Co hardmetals, it was concluded that the issues related to the EDM of WC-Co could be attributed to differences in physical properties such as melting and evaporation temperatures, thermal expansion and contraction coefficient and electrical conductivity. 5 EDM is based on high-voltage electrical 1 Norm Fasteners San. ve Tic.…”
Section: Introductionmentioning
confidence: 99%